The Metabolism of Islands - Singh, Simron; Fischer-Kowalski, Marina; Chertow, Marian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book makes the case for why we should care about islands and their sustainability. Islands are hotspots of biocultural diversity and home to 600 million people that depend on one-sixth of the earth's total area, including the surrounding oceans, for their subsistence. Today, they are at the frontlines of climate change and face an existential crisis. Islands are, however, potential "hubs of innovation" that are uniquely positioned to be leaders in sustainability and climate action. This volume argues that a full-fledged program on "island industrial ecology" is urgently needed, with the aim of offering policy-relevant insights and strategies to sustain small islands in an era of global environmental change. The nine contributions in this volume cover a wide range of applications of socio-metabolic research, from flow accounts to stock analysis and their relationship to services in space and time. They offer insights into how reconfiguring patterns of resource use will allow island governments to build resilience and adapt to the challenges of climate change.